Influence of benthic macrofauna community shifts on ecosystem functioning in shallow estuaries - Kristensen, Erik; Delefosse, Matthieu; Quintana, Cintia O.; Flindt, Mogens R.; Valdemarsen, Thomas (Frontiers in Marine Science, 2014)
We identify how ecosystem functioning in shallow estuaries is affected by shifts in benthic fauna communities. We use the shallow estuary, Odense Fjord, Denmark, as a case study to test our hypotheses that (1) shifts in benthic fauna composition and species functional traits affect biogeochemical cycling with cascading effects on ecological functioning, which may (2) modulate pelagic primary productivity with feedbacks to the benthic system. Odense Fjord is suitable because it experienced dramatic shifts in benthic fauna community structure from 1998 to 2008. We focused on infaunal species with emphasis on three dominating burrow-dwelling polychaetes: the native Nereis (Hediste) diversicolor and Arenicola marina, and the invasive Marenzelleria viridis. The impact of functional traits in the form of particle reworking and ventilation on biogeochemical cycles, i.e. sediment metabolism and nutrient dynamics, was determined from literature data. Historical records of summer nutrient levels in the water column of the inner Odense Fjord show elevated concentrations of NH4+ and NO3- (DIN) during the years 2004-2006, exactly when the N. diversicolor population declined and A. marina and M. viridis populations expanded dramatically. In support of our first hypothesis, we show that excess NH4+ delivery from the benthic system during the A. marina and M. viridis expansion period enriched the overlying water in DIN and stimulated phytoplankton concentration. The altered benthic-pelagic coupling and stimulated pelagic production may, in support of our second hypothesis, have feedback to the benthic system by changing the deposition of organic material. We therefore advice to identify the exact functional traits of the species involved in a community shift before studying its impact on ecosystem functioning. We also suggest studying benthic community shifts in shallow environments to obtain knowledge about the drivers and controls before exploring deep-water environments.